Battery with an acidified cathode and a lithium anode
By using acidified metal oxide nanomaterials in batteries and functionalizing their surface during synthesis, combining acidic electrolytes, the attack problem of acidic substances on battery components is solved, and a significant improvement in battery capacity and cycle life is achieved.
Patent Information
- Application Number
- JP2023110620
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-05-17
- Filing Date
- 2023-07-05
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2038-05-16
AI Technical Summary
In the prior art, acidic substances are prone to attack metal current collectors and housings in the battery, causing degradation of the electrode assembly, and the surface of the active catalyst will cause electrolyte to decompose, resulting in battery failure, while ignoring the impact of metal oxide surface properties on energy storage and battery performance.
Acidized metal oxide (AMO) nanomaterials are used as electrodes, and their surfaces are functionalized during synthesis through a single-kettle hydrothermal process to avoid super acidity, and combined with acidic electrolytes to improve battery performance, including the use of acidic electrolytes and electrode materials to enhance adsorption capacity to lithium ions.
The capacity, cycle characteristics and life of the battery are significantly improved, and the capacity increase of up to 100mAh/g and the charge and discharge cycle life of more than 100 times is achieved, avoiding battery failure caused by acidic substances in traditional technology.
Smart Images

Figure 0007628582000005 
Figure 0007628582000006 
Figure 0007628582000007
Abstract
Description
[Technical field]
[0001] Cross-references to related cases This application claims the benefit of U.S. Provisional Patent Application No. 62 / 507,659, filed May 17, 2017, entitled "BATTERY HAVING ACIDIFIED CATHODE AND LITHIUM ANODE," and incorporates such provisional application by reference into this disclosure as if they were fully set forth in this disclosure at this time.
[0002] The present disclosure is in the field of materials useful for chemical energy storage and power devices, such as, but not limited to, batteries. More specifically, the present disclosure relates to battery cells with cathodes and / or anodes comprising acidified metal oxide ("AMO") nanomaterials. In some embodiments, the battery cells are constructed with AMO cathodes and anodes consisting essentially of elemental lithium. [Background technology]
[0003] Metal oxides are compounds in which oxygen is bonded to a metal, m O x They are compounds with the general formula: They are found in nature but can be artificially synthesized. In synthetic metal oxides, the synthesis method can have a wide range of effects on the surface properties, including their acid / base properties. Changes in the surface characteristics can alter the properties of the oxide, affecting things like its catalytic activity and electron mobility. However, the mechanisms by which the surface controls reactivity are not always well characterized or fully understood. For example, in photocatalysis, surface hydroxyl groups are thought to facilitate the transfer of electrons from the conduction band to chemisorbed oxygen molecules.
[0004] Despite the importance of surface properties, the metal oxide literature, both academic papers and patents, has focused primarily on creating novel nanoscale crystalline forms of metal oxides to improve energy storage and power applications. Metal oxide surface properties have been neglected, and outside of the chemical catalysis literature, very little innovation has been directed toward controlling or modifying the surfaces of known metal oxides to achieve performance goals.
[0005] The chemical catalysis literature is dominated by pure sulfuric acid (18.4 M H 2 SO 4 ), which is often used for large-scale reactions such as the cracking of hydrocarbons. 2 SO 4 ), which cannot be measured on the conventional pH scale, but is instead quantified by the Hammett number. 0 ) can be thought of as extending the pH scale to negative numbers below zero. Pure sulfuric acid has a H of -12. 0 has.
[0006] However, there are many reaction systems and many applications where superacidity is too strong. For example, superacidity may degrade components of the system or catalyze undesirable side reactions. However, acidity may still be useful in these same applications because it provides enhanced reactivity and rate properties or enhanced electron mobility.
[0007] The battery literature teaches that acidic groups are detrimental to batteries, attacking metal current collectors and housings and potentially degrading other electrode components. Additionally, the prior art teaches that active catalytic electrode surfaces can lead to electrolyte decomposition, resulting in gassing inside the cell and ultimately causing cell failure.
[0008] Acidic, at least on its surface, but not super acidic, and the anode and / or cathode A need exists for battery packaging having a composite metal oxide disposed within the cathode. Additionally, existing battery construction technology should be updated to take full advantage of new and known materials available in accordance with the present disclosure. Summary of the Invention [Means for solving the problem]
[0009] This application describes materials corresponding to acidified metal oxides ("AMOs"), as well as uses of AMOs in batteries, such as battery electrode materials, catalysts, photovoltaic or photoactive components, and sensors. Techniques for making AMOs and devices containing AMOs are further disclosed. The disclosed AMOs may optionally be used in combination with acidic species to enhance their utility.
[0010] The present application further describes high capacity electrochemical cells comprising electrodes comprising metal oxides. Techniques for preparing metal oxides and electrochemical cells comprising metal oxides are further disclosed. Optionally, the disclosed metal oxides may be used in combination with conductive materials to form electrodes. The formed electrodes are useful for use with metallic lithium as a corresponding counter electrode and with conventional lithium ion electrodes. The disclosed metal oxides may be used in combination with acidic species to enhance their usefulness.
[0011] The described AMOs include those in the form of nanomaterials, such as nanoparticle forms, which can be monodisperse or substantially monodisperse, e.g., having a particle size of less than 100 nm. The disclosed AMOs, at certain concentrations (e.g., 5% by weight), when suspended in water or resuspended in water after drying, exhibit a low pH, such as less than 7 (e.g., between 0 and 7), and have a Hammett function H of greater than -12 (i.e., not super acidic), at least on the surface of the AMO. 0 Further shown.
[0012] The surface of the AMO may be optionally functionalized, such as with acidic or other electron-withdrawing species. Synthesis and surface functionalization may be accomplished in a "single-pot" hydrothermal method that functionalizes the surface of the metal oxide as it is synthesized from the appropriate precursors. In some embodiments, this single-pot method does not require any additional step or steps for acidification beyond those required to synthesize the metal oxide itself, and results in an AMO material with the desired surface acidity (but not super acidic).
[0013] Optionally, SO 4 , P.O. 4 Surface functionalization may be accomplished using strong electron withdrawing groups ("EWGs") such as halogens (Br, Cl, etc.), either alone or in combination with each other. Surface functionalization may also be accomplished using SO 4 , P.O. 4 , or EWGs that are weaker than halogens. For example, synthetic metal oxides can be used with acetate groups (CH 3 COO), oxalate group (C 2 O 4 ), and citrate groups (C 6 H 5 O 7 ) groups.
[0014] Despite conventional wisdom that acidic species are undesirable in batteries because they can attack metal current collectors and housings and cause degradation of other electrode components, and active catalytic electrode surfaces can lead to electrolyte decomposition, gassing within the cell, and ultimately cell failure, the inventors have discovered that acidic species and components can be advantageous in batteries that use AMO materials in the battery electrodes.
[0015] For example, the combination or use of AMOs with acidic species can improve the performance of the resulting material, system, or device, increasing the capacity, cycling characteristics, and lifespan of the device. As an example, batteries using AMO materials in combination with acidic electrolytes or electrolytes containing acidic species as described herein exhibit significant capacity increases, such as up to 100 mAh / g or more, over similar batteries using non-acidified electrolytes or electrolytes lacking acidic species. In some embodiments, improvements in capacity between 50-300 mAh / g can be achieved. In addition, absolute capacities of up to 1000 mAh / g or more can be achieved using batteries having acidified electrolytes or electrolytes containing acidic species. Furthermore, the cycle life of the battery can be improved with the use of acidic electrolytes or electrolytes containing acidic species, such that the cycle life of the battery is extended up to 100 or more charge / discharge cycles.
[0016] Additionally or alternatively, batteries containing electrodes, such as cathodes or anodes, that are themselves acidic or contain acidic species, such as organic acids, may also be beneficial, again going against conventional teachings in battery technology. For example, batteries incorporating acidic electrodes or acidic species within the electrodes may improve performance and increase capacity, cycling characteristics, and life, especially when used with electrodes containing AMO materials. Capacity increases of up to 100 mAh / g or more can be achieved. The cycle life of the battery may also be improved with the use of acidic electrodes or electrodes containing acidic species, such as when the cycle life of the battery is extended by up to 100 cycles or more. As an example, an acidic electrode or an electrode containing acidic species may exhibit a pH of less than 7 (but not super acidic), such as when the components of the electrode are suspended in water (or resuspended in water after drying) at 5% by weight.
[0017] An electrode according to the present disclosure may include a layered structure including a first set of layers including a conductive material and a second set of layers including a metal oxide, such as an acidified metal oxide (AMO) nanomaterial. Optionally, the first set of layers and the second set of layers may be provided in an alternating configuration. Optionally, the first set of layers and the second set of layers may independently include 1 to 20 layers. Optionally, the first set of layers and the second set of layers may independently have a thickness between 1 μm and 50 μm, between 2 μm and 25 μm, between 3 μm and 20 μm, between 4 μm and 15 μm, or between 5 μm and 10 μm. Optionally, the metal oxide comprises between 5 and 90 weight percent of the set of second layers, e.g., 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, or 90 weight percent of the set of second layers. Optionally, the conductive material and the binder may each independently comprise between 5 and 90 weight percent of the set of first layers, e.g., 25, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, or 90 weight percent of the set of first layers.
[0018] The first electrode may optionally include a metal oxide up to 95 weight percent of the first electrode, up to 80 weight percent of the first electrode, up to 70 weight percent of the first electrode, between 1-50 weight percent of the first electrode, between 1-33 weight percent of the first electrode, between 15-25 weight percent of the first electrode, between 55-70 weight percent of the first electrode, between 20-35 weight percent of the first electrode, between 5-15 weight percent of the first electrode. Specific examples of metal oxide weight percent of the first electrode include 1%, 5%, 11%, 12%, 13%, 14%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 60%, 61%, 62%, 63%, 64%, 65%, etc. Optionally, the conductive material and binder may each independently comprise the majority of the remainder of the first electrode. For example, the conductive material and binder may each independently comprise between 10 and 74 weight percent of the first electrode. Optionally, the conductive material and binder may each together comprise between 20 and 90 weight percent of the first electrode. Optionally, the AMO nanomaterial may be added as a dopant at 1 to 10 weight percent to a conventional lithium ion electrode, such as graphite, lithium cobalt oxide, etc.
[0019] A variety of materials are useful in the electrodes described herein. Examples of metal oxides include, but are not limited to, lithium-containing oxides, aluminum oxide, titanium oxide, manganese oxide, iron oxide, zirconium oxide, indium oxide, tin oxide, antimony oxide, bismuth oxide, or any combination thereof. Optionally, the oxide is in the form of AMO. As described herein, the metal oxides include Cl, Br, BO, 3 , S.O. 4 , P.O. 4 , NO 3 , C.H. 3 COO, C 2 O 4 , C 2 H 2 O 4 , C 6 H 8 O 7, or C 6 H 5 O 7 and / or may be surface-functionalized with one or more electron-withdrawing groups selected from: Exemplary conductive materials include one or more of graphite, conductive carbon, carbon black, Ketjen black, or conductive polymers such as poly(3,4-ethylenedioxythiophene) (PEDOT), polystyrene sulfonate (PSS), PEDOT:PSS composites, polyaniline (PANI), or polypyrrole (PPY).
[0020] In some embodiments, an electrode comprising an AMO nanomaterial is used in combination with another electrode to form a cell. For example, the second electrode of such a cell may comprise graphite, lithium metal, sodium metal, lithium cobalt oxide, lithium titanate, lithium manganate, lithium nickel manganese cobalt oxide (NMC), lithium iron phosphate, lithium nickel cobalt aluminum oxide (NCA), the AMO nanomaterial, or any combination thereof. In certain embodiments, the first electrode is SnO 2 and the second electrode comprises metallic lithium.
[0021] A variety of materials are useful in the electrodes described herein. Examples of metal oxides include, but are not limited to, lithium-containing oxides, aluminum oxide, titanium oxide, manganese oxide, iron oxide, zirconium oxide, indium oxide, tin oxide, antimony oxide, bismuth oxide, or any combination thereof. Optionally, the oxide may be in the form of AMO. As described herein, metal oxides include, but are not limited to, Cl, Br, BO, 3 , S.O. 4 , P.O. 4 , NO 3 , C.H. 3 COO, C 2 O 4 , C 2 H 2 O 4 , C 6 H 8O 7 , or C 6 H 5 O 7 The conductive material may optionally include and / or be surface-functionalized with one or more electron-withdrawing groups selected from: Exemplary conductive materials include one or more of graphite, conductive carbon, carbon black, Ketjen black, or conductive polymers such as poly(3,4-ethylenedioxythiophene) (PEDOT), polystyrene sulfonate (PSS), PEDOT:PSS composites, polyaniline (PANI), or polypyrrole (PPY).
[0022] As a further example, batteries in which electrodes are formed using slurries may also be beneficial and may go against conventional teachings in battery technology. As described herein, AMO materials may be formed into battery electrodes by first forming a slurry of the AMO materials, optionally including one or more binder compounds, solvents, additives (e.g., conductive or acidic additives), and / or other wet processing materials. The slurry may be deposited onto a conductive material or current collector to form an electrode. Such slurries and / or solvents may optionally be acidic or include acidic species, again which may allow for improved capacity, cycling characteristics, and life of the resulting battery. Optionally, all or a portion of the solvent may be evaporated, leaving behind the AMO materials, binders, additives, etc. The resulting material may optionally exhibit its own acidity, such as having a pH of less than 7 (but not super acidic) when suspended in water (or resuspended in water after drying) at 5 wt.%.
[0023] Various techniques can be used to make the metal oxide. Optionally, the process of making the metal oxide may include forming a solution containing a metal salt, ethanol, and water, acidifying the solution by adding an acid to the solution, basifying the solution by adding an aqueous base to the solution, collecting a precipitate from the solution, washing the precipitate, and drying the precipitate.
[0024] Optionally, the step of fabricating an electrode may further include forming a conductive layer on the electrode layer, such as a conductive layer comprising a second conductive material. The method may further include depositing a conductive layer comprising a conductive material and a binder. Optionally, depositing the conductive layer may include forming a conductive slurry using a second conductive material, a second binder, and a second solvent, depositing the conductive slurry layer on the electrode layer, and evaporating at least a portion of the second solvent to form the conductive layer. Optionally, fabricating the electrode may include forming 1-20 additional conductive layers comprising a conductive material, and 1-20 additional electrode layers comprising a metal oxide. For example, the electrode may include a layered structure comprising a first set of layers comprising the second conductive material and a second set of layers comprising a metal oxide, the first set of layers and the second set of layers being provided in an alternating configuration. Exemplary layers include layers independently having a thickness between 1 μm and 50 μm. Exemplary layers include layers comprising between 10 and 90 weight percent metal oxide. Exemplary layers include layers independently comprising between 5 and 85 weight percent conductive material and / or binder.
[0025] Electrodes formed using the method of this embodiment may have a metal oxide content of up to 80 percent by weight. Electrodes formed using the method of this embodiment may have a conductive material and / or binder content of between 10 and 70 percent by weight of the electrode.
[0026] As noted above, the acidic species may optionally be included as an additive in any of the battery's components, such as the electrodes or the electrolyte. Optionally, a battery containing AMO may include an electrolyte disposed between the electrodes in which the acidic species is dissolved in a solvent. Such an electrolyte may also be referred to herein as an acidified electrolyte. The electrolyte may be LiPF 6 , LiAsF 6 , LiClO 4 , LiBF 4 , LiCF 3 SO 3and combinations thereof. It will be appreciated that the electrolyte may be disposed in the space separating the electrodes (i.e., between the electrodes) and may also impregnate or permeate the pores of the electrodes and / or the pores of any material or structure optionally disposed between the electrodes, such as a separator.
[0027] Examples of acidic species useful with the AMOs, electrodes, and electrolytes described herein include, but are not limited to, organic acids, such as carboxylic acids. Examples of acidic species include those that exhibit a pKa in water between -10 and 7, between -5 and 6, between 1 and 6, between 1.2 and 5.6, or about 4. Specific examples of organic acids include, for example, oxalic acid, carbonic acid, citric acid, maleic acid, methylmalonic acid, formic acid, glutaric acid, succinic acid, methylsuccinic acid, methylenesuccinic acid, citraconic acid, acetic acid, and benzoic acid. Examples of organic acids include dicarboxylic acids, such as
[0028] [ka] Formula (wherein R is a substituted or unsubstituted C1-C20 hydrocarbon, such as a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, a substituted or unsubstituted aromatic or heteroaromatic group, or a substituted or unsubstituted amine). Examples of organic acids include:
[0029] [ka] Formula (In the formula, L is a substituted or unsubstituted C1-C1-C2 alkylene group, a substituted or unsubstituted arylene group, a substituted or unsubstituted heteroarylene group, a substituted or unsubstituted amine, or the like.) The organic acid may also include organic acid anhydrides, such as those having a C20 divalent hydrocarbon.
[0030] [ka] Formula (wherein R1 and R2 are independently substituted or unsubstituted C1-C20 hydrocarbons, such as substituted or unsubstituted alkyl groups, substituted or unsubstituted alkenyl groups, substituted or unsubstituted aromatic or heteroaromatic groups, substituted or unsubstituted amines). Optionally, R1 and R2 can form a ring. Examples of organic acid anhydrides include anhydrides of any of the organic acids mentioned above. Specific organic acid anhydrides include, but are not limited to, glutaric anhydride, succinic anhydride, methylsuccinic anhydride, maleic anhydride, and itaconic anhydride.
[0031] Useful concentrations of acidic species in either or both of the electrolyte and the AMO electrode include 0% to 10% by weight, 0.01% to 10% by weight, 0.1% to 10% by weight, 1% to 5% by weight, or 3% to 5% by weight.
[0032] Useful solvents include, for example, those used in lithium ion battery systems, such as ethylene carbonate, butylene carbonate, propylene carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, fluoroethylene carbonate, and mixtures thereof. Other useful solvents will be understood by those skilled in the art. Optionally, when an acidic species and a metal salt are dissolved in the solvent to form an electrolyte, the electrolyte itself may exhibit acidic conditions (i.e., a pH of less than 7).
[0033] Examples of binders useful in the batteries and electrodes described herein include styrene butadiene copolymer (SBR), polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), acrylonitrile, polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyamideimide (PAI), and any combination thereof. Optionally, conductive polymers may be useful as binders.
[0034] Other examples of additives useful in the AMOs and electrodes described herein include, but are not limited to, conductive additives. Examples of conductive additives include graphite, conductive carbon, carbon black, Ketjen black, and conductive polymers such as poly(3,4-ethylenedioxythiophene (PEDOT), polystyrene sulfonate (PSS), PEDOT:PSS composites, polyaniline (PANI), and polypyrrole (PPY). The conductive additive may be present in the electrode at any suitable concentration, such as, for example, a weight percent of from greater than 0 to as much as 35 weight percent, 40 weight percent, or more. Optionally, the conductive additive may be present in the electrode at a concentration of from 1 weight percent to 95 weight percent. The amount may be present in the ranges of 1% to 35% by weight, 1% to 25% by weight, 5% to 40% by weight, 10% to 40% by weight, 15% to 40% by weight, 20% to 40% by weight, 25% to 40% by weight, 30% to 40% by weight, 35% to 40% by weight, 40% to 45% by weight, 40% to 50% by weight, 40% to 55% by weight, 40% to 60% by weight, 40% to 65% by weight, 40% to 70% by weight, 40% to 75% by weight, 40% to 80% by weight, 40% to 85% by weight, 40% to 90% by weight, or 40% to 95% by weight.
[0035] Methods of making batteries are also described herein. An example method of making a battery includes making an AMO nanomaterial, forming a first electrode of or including an AMO nanomaterial, forming an electrolyte by dissolving one or more metal salts in a solvent, and disposing the electrolyte between the first electrode and a second electrode. Another example method of making a battery includes making an AMO nanomaterial, forming a first electrode of or including an AMO nanomaterial and one or more metal salts in a solvent, and disposing the electrolyte between the first electrode and a second electrode.
[0036] Also disclosed herein is an electrolyte for use in a battery. For example, the disclosed electrolyte is useful in a battery comprising a first electrode and a second electrode, such as a first electrode comprising an acidified metal oxide (AMO) nanomaterial. An example electrolyte comprises a solvent and one or more metal salts dissolved in the solvent. Optionally, an acidic species, such as an acidic species different from the one or more metal salts, is dissolved in the solvent.
[0037] As described above, a variety of acidic species are useful in the disclosed electrolytes, including acidic species including organic acids and / or organic acid anhydrides. Examples of organic acids include, but are not limited to, oxalic acid, acetic acid, citric acid, maleic acid, methylmalonic acid, glutaric acid, succinic acid, methylsuccinic acid, methylenesuccinic acid, citraconic acid, or any combination thereof. Examples of organic acid anhydrides include, but are not limited to, glutaric anhydride, succinic anhydride, methylsuccinic anhydride, maleic anhydride, itaconic anhydride, or any combination thereof. Examples of other acidic species are as described above. Useful acidic species include, but are not limited to, those exhibiting a pKa between -10 and 7, between -5 and 6, between 1 and 6, between 1.2 and 5.6, or about 4. The acidic species may optionally be present in the electrolyte at any suitable concentration, such as 0.01% to 10% by weight, 0.1% to 10% by weight, 1% to 5% by weight, or 3% to 5% by weight.
[0038] LiPF 6 , LiAsF 6 , LiClO 4 , LiBF 4 , LiCF 3 SO 3It will be understood that lithium metal salts such as may be useful components of the disclosed acidified electrolyte. Examples of solvents include, but are not limited to, ethylene carbonate, butylene carbonate, propylene carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, fluoroethylene carbonate, and mixtures thereof. Examples of solvents may be useful in metal ion batteries, such as lithium ion batteries. [Brief description of the drawings]
[0039] [Figure 1] FIG. 1 is a simplified cross-sectional view of an exemplary lithium-ion battery cell. [Diagram 2] FIG. 2 is another simplified cross-sectional view of a lithium-ion battery cell in which the electrolyte is substantially contained by the separator. [Diagram 3] FIG. 1 is a schematic diagram of a lithium ion battery containing multiple cells. [Figure 4] 1 shows the difference in the cyclic voltammograms of AMO tin prepared by the methods disclosed herein compared to the cyclic voltammograms of commercially available non-AMO tin when cycled against Li. [Diagram 5] It is shown that the total reflectance of AMO tin oxide differs from that of commercial non-AMO tin oxide. [Figure 6] 1 is X-ray photoelectron spectroscopy (XPS) data showing surface functionalization that occurs intrinsically from the synthesis methods disclosed herein. The numbers shown are atomic concentrations in %. The rightmost column lists the corresponding pH of the synthesized nanoparticles measured when dispersed at 5 wt % in aqueous solution. [Figure 7] Electron microscopy images are provided showing the differences in morphology between AMO nanoparticles synthesized under identical conditions except for using different groups for functionalization. [Figure 8] FIG. 1 shows the differences in morphology and performance of AMO nanoparticles synthesized under identical conditions but with two different total reaction times. [Figure 9]Representative half-cell data are provided that show the difference in behavior towards lithium between spherical and elongated (needle-like or rod-like) AMOs upon cycling. [Figure 10] We provide X-ray photoelectron spectroscopy analysis of the surface of AMO nanoparticles synthesized using both strong (phosphorus-containing) and weak (acetate) electron-withdrawing groups, showing a higher atomic concentration of phosphorus than the bonds associated with acetate groups. [Figure 11A] Data are provided showing visible light activated degradation data of different AMOs. [Figure 11B] Data are provided showing the UV-activated degradation data of different AMOs. [Figure 12] 1 is a graph comparing two AMOs, one with higher capacity for use in primary (single use) battery applications and the other with higher cycling characteristics for use in secondary (rechargeable) battery applications. [Figure 13] Charge / discharge capacity data and coulombic efficiency data are provided, showing that AMO can enhance battery performance without degradation of battery components or gassing. [Figure 14] Capacity and cycling data for AMO in standard, acidified, and basified electrolyte systems are shown. [Figure 15] Capacity and cycle data for the AMO and the same AMO where the acidification was removed by solvent washing are shown. [Figure 16] Data is provided including plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include AMO materials. [Figure 17] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Figure 18]Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Figure 19] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Figure 20] Data is provided including plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include AMO materials. [Figure 21] Data is provided including plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include AMO materials. [Figure 22] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Figure 23] Data is provided including plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include AMO materials. [Figure 24] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Diagram 25] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Figure 26] Data is provided including plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include AMO materials. [Figure 27] Data is provided including electron microscope images of the composite material, as well as plots of measured capacity versus cycle number and plots of voltage as a function of time during cycling for battery cells including electrodes that include the composite material. [Figure 28] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Figure 29] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Diagram 30] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Diagram 31] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Diagram 32] Data is provided including plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include AMO materials. [Diagram 33] Data is provided including plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include AMO materials. [Diagram 34] Data is provided including plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include AMO materials. [Diagram 35]Data is provided including plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include AMO materials. [Diagram 36] Data is provided including plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include AMO materials. [Figure 37] Data is provided including plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include AMO materials. [Figure 38] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Figure 39] Data is provided including plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include AMO materials. [Diagram 40] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Diagram 41] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Diagram 42] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Diagram 43] Data is provided including plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include AMO materials. [Diagram 44] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Diagram 45] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Diagram 46] Data are provided including electron microscope images of the AMO materials, as well as plots of measured capacity versus cycle number, and plots of voltage as a function of time during cycling, for battery cells including electrodes that include the AMO materials. [Figure 47] 1 is a plot of temperature and voltage for a cell constructed in accordance with the present disclosure and subjected to a nail penetration test. [Figure 48A] 1 is a plot of temperature and voltage of a cell constructed in accordance with the present disclosure and subjected to overcharge testing. [Figure 48B] FIG. 48B is a plot of the overcharge test of FIG. 48A focusing on the start of the test.
[0040] definition For purposes of this disclosure, the following terms have the following meanings.
[0041] Acid oxide - a term commonly used in the scientific literature to refer to binary compounds of nonmetallic elements and oxygen. An example is carbon dioxide, CO 2 The oxides of some metalloids (e.g., Si, Te, Po) also have weak acidic properties in the pure molecular state.
[0042] Acidified Metal Oxide ("AMO") - a term used herein to mean a binary compound of a metal element and oxygen, which has an acidity higher than that of its natural mineral state and has a Hammett function, H 0>-12 (not super acidic) and have an average particle size smaller than that of the natural mineralogical state. Naturally occurring mineralogical forms are not included within the scope of the AMO materials of the present invention. However, synthetic metal oxides that are more acidic than the most abundant naturally occurring (of equivalent stoichiometry) mineralogical forms, but are not super acidic, are included within the scope of the present disclosure and may be said to be AMO materials if they meet certain other conditions discussed in this disclosure.
[0043] Acidic - A term commonly used in the scientific literature to refer to compounds that have a pH of less than 7 in aqueous solution.
[0044] Electron Withdrawing Group ("EWG") - an atomic or molecular group that attracts electron density to itself. The strength of an EWG is based on its known behavior in chemical reactions. For example, halogens are known to be strong EWGs. Organic acid groups such as acetate are known to be weakly electron withdrawing.
[0045] Hammett function - an additional means of quantifying acidity in highly concentrated acidic solutions and superacids, where the acidity is defined by the following equation: H 0 =pK BH+ +log([B] / [BH + On this scale, 18.4 moles of pure H 2 SO 4 is -12 H 0 H for pure sulfuric acid 0 The value of =-12 should not be interpreted as pH=-12, but rather it is a value where the acid species present is 10 12 H at a hypothetical (ideal) concentration in mol / L 3 O + This means that the proton addition ability is equivalent to that of the Hammett acidity function. The Hammett function avoids water in the equation. It is used herein to provide a quantitative means of distinguishing between AMO materials and superacids. The Hammett function can be correlated with colorimetric reagent tests and temperature programmed desorption results.
[0046] Metal oxide - a term commonly used in academic literature to refer to binary compounds of metallic elements and oxygen. Depending on their position in the periodic table, metal oxides range from weakly basic to amphoteric (exhibiting both acidic and basic properties) in their pure molecular state. Weakly basic metal oxides are the oxides of lithium, sodium, magnesium, potassium, calcium, rubidium, strontium, indium, cesium, barium and tellurium. Amphoteric oxides are the oxides of beryllium, aluminum, gallium, germanium, astatine, tin, antimony, lead and bismuth.
[0047] Monodisperse--characterized by particles of uniform size that are substantially separate from one another and not agglomerated into grains of larger particles.
[0048] pH - a numerical scale of functions commonly used in scientific literature to specify the acidity or alkalinity of an aqueous solution. It is the function of the hydronium ion [H 3 O +
[0046] As used herein, it describes the relative acidity of nanoparticles suspended in an aqueous solution.
[0049] Surface functionalization - The attachment of small atomic or molecular groups to the surface of a material.
[0050] Super Acid - 100% H 2 SO 4 It is more acidic than H 0 A material with a Hammett function of <-12. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0051] Referring now to FIG. 1, a lithium-ion battery cell 100 is shown in a simplified cross-sectional view. The cell 100 may include a casing or container 102. In some embodiments, the casing 102 is a polymer or alloy. The casing 102 chemically and electrically isolates the contents of the cell 100 from adjacent cells, from contamination, and from damage or from other components of the device in which the cell 100 is installed. A complete battery may include multiple cells arranged in series and / or parallel configurations. The battery may have additional casings or fastening mechanisms that join multiple cells together, as known in the art.
[0052] The cell 100 provides a cathode 104 and an anode 106. The contents of the cell 100 undergo a chemical reaction when a conductive path is provided between the cathode 104 and the anode 106 that is external to the cell 100. As a result of the chemical reaction, electrons are provided at the anode 106, and these electrons flow to the cathode 104 through a circuit (sometimes called a load) that is external to the battery. At a basic level, during discharge of the cell 100, the materials that comprise the anode 106 are oxidized, providing the electrons that flow through the circuit. As a recipient of the electrons released by the anode 106, the materials that comprise the cathode 104 are reduced.
[0053] In the cell 100, during discharge, metal cations migrate through the electrolyte 108 from the anode 106 to the cathode 104. In the case of lithium-based batteries, the metal cations are lithium cations (Li + The electrolyte 108 can be a lithium salt in an organic solvent (e.g., LiClO in ethylene carbonate). 4 ) or other liquid electrolyte. Other lithium-based electrolyte / solvent combinations known in the art may be used. In some cases, the electrolyte 108 may be a solid electrolyte, such as a lithium salt in polyethylene oxide. Optionally, the electrolyte may include a polymer electrolyte. Examples of electrolytes include those disclosed in U.S. Pat. No. 6,393,311, which are incorporated herein by reference. Included are the electrolytes described in Patent Application Publication No. 2017 / 0069931.
[0054] A separator 110 may be used to prevent contact between the electrodes 104, 106. The separator 110 may be a porous layer material that is permeable to lithium ions and the electrolyte 108, but is not otherwise conductive, to prevent internal shorting of the cell 100. As is known in the art, the separator 110 may include glass fibers or optionally a polymer having a semi-crystalline structure. Additional components, such as current collectors, may also be included in the cell 100, but are not shown in FIG. 1.
[0055] Together, the anode 104, cathode 106, electrolyte 108, and separator 110 form the complete cell 100. Because the separator 110 is porous, the electrolyte 108 can flow into or be contained within the separator 110. Under normal operating conditions, the porosity of the separator 110 allows the ions (Li + ) is allowed to flow between the electrodes 104, 106 via the electrolyte 108. As is known in the art, the separator can be constructed such that if exposed to an excess of heat or a runaway exothermic reaction, the internal pore structure will melt and close, shutting down the cell.
[0056] Most lithium-based batteries are so-called secondary batteries. Secondary batteries can be discharged and recharged many times until the chemical or structural integrity of the cell falls below acceptable limits. Cells and batteries according to the present disclosure are considered to be both primary (e.g., single-use) and secondary batteries.
[0057] In the case of cell 100 being a secondary battery (or part of a secondary battery), it should be understood that cell 100 may be recharged alone or as a component of a complete system in which multiple cells are recharged simultaneously (and possibly in the same parallel or series circuit).
[0058] To effect charging, a reverse voltage is applied to the cell 100. It should be understood that various schemes for effectively recharging a lithium battery can be used. Constant current, variable current, constant voltage, variable voltage, partial duty cycle, etc. may be used. This disclosure is not intended to be limited to any particular charging method unless otherwise stated in the claims. During charging of the cell 100, element 115 represents a voltage source that is applied between the cathode 104 and the anode 106 to provide electrons from the cathode 105 to the anode 106, allowing a chemical reaction to occur. Lithium ions fold back from the cathode 104 to the anode 106 through the electrolyte 108 and the separator 110.
[0059] As an example, the cathode 104 or anode 106 may independently comprise an AMO material disclosed herein. When an AMO material is used as the cathode, the anode may correspond to a lithium intercalation material such as lithium metal or graphite. Optionally, the electrolyte 108 may comprise an acidic species dissolved in an organic solvent along with a lithium salt. In addition to or as an alternative to the use of an acidic species in the electrolyte 108, an electrode (i.e., the cathode 104 or anode 106) may optionally comprise an AMO and an acidic species. Oxalic acid is an exemplary acidic species.
[0060] Without wishing to be bound by any theory, it is believed that the presence of acidic species in the cathode 104 or anode 106 and / or electrolyte 108 improves the surface affinity of the AMO material for lithium ions, which in turn improves its ability to absorb lithium ions during discharge, resulting in an overall improved capacity compared to a similar cell lacking acidic species or having a basified electrode or electrolyte (i.e., including basic species). Alternatively, or in addition, the presence of acidic species may allow additional active sites for lithium absorption at the cathode 104.
[0061] It should be understood that FIG. 1 is not to scale. As shown in FIG. 2, in most applications, the separator 110 occupies most or all of the space between and is in contact with the electrodes 104, 106. In such cases, the electrolyte 108 is contained within the separator 110 (although it may also penetrate into the pores or surfaces of the anode or cathode). FIG. 2 is also not necessarily to scale. The actual geometry of the cell can range from a relatively thin, flat pouch to a canister-type structure, button cell, and the like. Cell construction techniques such as wound or bobbin-type or pin-type assemblies may be used.
[0062] Current collectors and other components (not shown) known in the art can also be included to form the cell 100 into a commercially usable package. Although the overall shape or geometry may vary, a cell or battery typically includes electrodes 104, 106 that are separated rather than touching at some location or cross-section, with an electrolyte 108 and optionally a separator 110 between the electrodes 104, 106. Cells may also be constructed such that there are multiple layers of anodes and cathodes. Cells may also be configured such that two cathodes are on opposite sides of a single anode, or vice versa.
[0063] A functional or operable battery intended for a particular purpose may comprise multiple cells arranged according to the needs of a particular application. An example of such a battery is shown diagrammatically in FIG. 3, where the battery 300 includes four lithium cells 100 arranged in series to increase the voltage. The capacity can be increased at this voltage by providing an additional stack of four cells 100 in parallel with the stack shown. Different voltages can be achieved by varying the number of cells 100 arranged in series.
[0064] The positive electrode 306 may be accessible outside the casing 302 of the battery 300. A negative electrode 304 is also provided. The physical form factor of the electrodes 304, 306 may vary depending on the application. Various binders, adhesives, tapes, and / or other fastening mechanisms (not shown) may be used within the battery casing 302 to stabilize the other components. Batteries based on lithium technology are generally operable, rechargeable, and storable (if secondary) in either orientation. As noted above, the cell 100 may take on a variety of different geometric shapes. Thus, FIG. 3 is not intended to represent a particular physical form factor of the battery 300.
[0065] The battery 300 may also include various auxiliary circuits 308 disposed within the casing 302 of the battery 300 between the positive terminal 308 and the lithium cell 100. In other embodiments, the auxiliary circuits are disposed between the negative terminal 304 and the lithium battery 100 instead of, or in addition to, being disposed between the positive terminal 306 and the lithium battery 100. The auxiliary circuits 308 may include short circuit protection, overcharge protection, overtemperature shutdown, and other circuits known in the art for protecting the battery 300, the cells 100, and / or any load attached to the battery 300.
[0066] The composition of materials selected for the cathode 104, anode 106, and electrolyte can be important to the performance of the cell 100 and any battery of which it forms a part. In the context of this disclosure, various examples of AMOs and their methods of manufacture are provided in this regard. These AMOs are suitable for use in forming anodes or cathodes in half cells, cells, and batteries. The AMOs of the present disclosure are otherwise compatible with known lithium cell technology, including existing anode compositions, cathode compositions, electrolyte formulations, and separator compositions.
[0067] In the context of the present disclosure, various examples of AMOs and their methods of manufacture and use are provided. These AMOs are suitable for use in forming cathodes or anodes in half cells, cells, and batteries. The disclosed AMOs are compatible with conventional lithium battery technology, including otherwise existing anode compositions, cathode compositions, electrolyte formulations, and separator compositions. It will be understood that the anode 106 material selected for a cell or battery according to the present disclosure may be less electronegative than the material of the cathode and may suitably complement the cathode material. In one particular embodiment, the disclosed AMOs are useful as cathodes in cells having metallic lithium anodes.
[0068] In various embodiments of the present disclosure, the cathode 104 comprises an AMO material having an acidic, but not super acidic, surface. This may be in contrast to materials previously known and utilized as cathodes, such as lithium cobalt or lithium manganese materials. The AMO materials of the present disclosure and their methods of manufacture are described below. In other embodiments, the anode 106 comprises an AMO material of the present disclosure having an acidic, but not super acidic, surface.
[0069] Metal oxide surfaces are ideally arrays of metal and oxygen centers, aligned according to the oxide's crystal structure. In reality, the array is imperfect and prone to vacancies, distortions, and surface deposits. Regardless, all exposed metal centers are cationic (positively charged) and can accept electrons, and therefore function as Lewis acid sites by definition. The oxygen centers are anionic (negatively charged) and act as Lewis basic sites that donate electrons. This gives rise to the familiar amphoteric nature of metal oxide surfaces.
[0070] Under normal atmospheric conditions, water vapor present will adsorb on the surface of metal oxides either in molecular form (hydrated) or in dissociated form (hydroxylated). OH - Seed and H +Both species can be adsorbed on the oxide surface. The negatively charged hydroxyl species binds to the cationic (Lewis acid, electron accepting) center of the metal and forms H + binds to the anion (Lewis base, electron donating) center of oxygen. Both adsorptions result in the presence of the same functional group - hydroxyl - on the metal oxide surface.
[0071] These surface hydroxyl groups can either give up or accept a proton and therefore can function as either Bronsted acids or Bronsted bases. The tendency of an individual hydroxyl group to be a proton donor or acceptor is influenced by the coordination of the metal cation or oxygen anion to which it is bound. Metal oxide surface defects such as oxygen vacancies, or coordination to surface groups by other species, mean that not all cations and anions are coordinated equally. Acid and base sites vary in number and strength. When "aggregated" broadly across the surface of an oxide, this can give the surface an overall acidic or basic character.
[0072] The amount and strength of Lewis acid and base sites (from exposed metal cations and oxygen anions, respectively) and Brønsted acid and base sites (from surface hydroxyl groups) add a wide range of utility and functionality to metal oxides and their use in both chemical reactions and device applications. These sites contribute significantly to the chemical reactivity of metal oxides. They can function as anchor points to which other chemical groups, even additional metal oxides, can be attached. They can also affect surface charge, hydrophilicity, and biocompatibility.
[0073] One way to modify the surface of metal oxides is to attach small chemical groups, or electron-withdrawing groups ("EWGs"), in a process known as surface functionalization. EWGs induce polarization of hydroxide bonds, promoting hydrogen dissociation. For example, stronger EWGs result in more cleaved surfaces. This should result in polarized bonds and therefore more acidic protons. The acidity of a Lewis point can be increased by inducing a polarization that favors the donation of electrons to the point. If the compound so made is placed in water, the acidic protons will dissociate, thus lowering the measured pH of the water.
[0074] Although somewhat imprecise when working with solid rather than liquid acid / base systems, traditional pH measurement methods utilizing titration, pH paper, and pH probes can be used to assess the acidity of metal oxides dispersed in aqueous solutions. These measurements can be supplemented using techniques including, but not limited to, colorimetric reagents, infrared spectroscopy, and temperature programmed desorption data to establish the acidified nature of the metal oxide surface. Surface groups can be examined by standard analytical techniques including, but not limited to, X-ray photoelectron spectroscopy.
[0075] Surface functionalization can be accomplished post-synthesis, including but not limited to exposing the metal oxide to an acidic solution or to a vapor containing the desired functional group. It can also be accomplished by solid-phase methods, in which the metal oxide is mixed and / or ground with a solid containing the desired functional group. However, all of these methods require one or more additional surface functionalization steps beyond those required to synthesize the metal oxide itself.
[0076] The synthesis and surface functionalization of the AMO material may be accomplished by a "single-pot" hydrothermal synthesis method or equivalent, where the surface of the metal oxide is functionalized as it is synthesized from the appropriate precursor. The salt of the precursor containing the EWG is solubilized, and the resulting solution is acidified with an acid containing a second EWG. The acidified solution is basified, and the basified solution is heated and then washed. A drying step produces the solid AMO material.
[0077] As an example, a preferred embodiment of tin oxide in the AMO form was synthesized and simultaneously surface functionalized using the following single-pot method.
[0078] 1. First, seven grams (7 g) of tin(II) chloride dihydrate (SnCl 2 2H 2 O) is dissolved in a solution of 35 mL of absolute ethanol and 77 mL of distilled water.
[0079] 2. Stir the resulting solution for 30 minutes.
[0080] The solution is acidified by dropwise addition of 3.7 mL of 1.2 M HCl and the resulting solution is stirred for 15 min.
[0081] The solution is basified by dropwise addition of 4.1 M aqueous base until the pH of the solution is approximately 8.5.
[0082] 5. The resulting opaque white suspension is then placed in a water bath (approximately 60-90°C) with stirring for at least 2 hours.
[0083] 6. The suspension is then washed with distilled water and absolute ethanol.
[0084] 7. The washed suspension is dried in air at 100° C. for 1 hour and then annealed in air at 200° C. for 4 hours. This method yields tin AMOs surface-functionalized with chlorine, whose pH is about 2 when measured by resuspension at room temperature in aqueous solution at 5 wt %. By definition, their Hammett function is H 0 >-12. Here we are describing an open system such as a flask, A closed system such as an autoclave may be used.
[0085] Using the single-pot method disclosed above, several AMOs have been synthesized. Table 1 below describes the precursors and acids used. In some cases, dopants are utilized as well:
[0086] [Table 1] In some embodiments, the electron withdrawing group has a carbon chain length of 6 or less and / or an organic mass (AMU) of 200 or less. In some embodiments, the electron withdrawing group has a carbon chain length of 8 or less or 10 or less and / or an organic mass of 500 or less.
[0087] It will be understood that the parameters of the method can be varied. These parameters include, but are not limited to, the type and concentration of reagents, the type and concentration of acid and base, reaction time, temperature and pressure, agitation speed and time, number and type of washing steps, drying and calcination time and temperature, and exposure to gas during drying and calcination. Variations may be performed alone or in any combination, optionally using experimental design techniques. Additionally, other metal oxide synthesis methods - e.g., spray pyrolysis, vapor deposition, electrodeposition, solid-state methods, and hydrothermal or solvothermal processes - may be used in conjunction with the methods disclosed herein. may be useful for achieving the same or similar results as in the method.
[0088] A variety of annealing conditions are useful for the preparation of AMO nanomaterials. Exemplary annealing temperatures can be below 300°C, e.g., 100°C to 300°C. Exemplary annealing times can range from about 1 hour to about 8 hours or more. Annealing can be performed under a variety of atmospheric conditions. For example, annealing can be performed in air at atmospheric pressure. Annealing can be performed under high pressure (higher than atmospheric pressure) or under reduced pressure (lower than atmospheric pressure or in a vacuum). Alternatively, annealing can be performed in a controlled atmosphere, such as under an inert gas (e.g., nitrogen, helium, or argon) or in the presence of an oxidizing gas (e.g., oxygen or water).
[0089] A variety of drying conditions are useful for the preparation of AMO nanomaterials. Exemplary drying temperatures can be from 50° C. to 150° C. Exemplary drying times can range from about 0.5 hours to about 8 hours or more. Drying can be performed under a variety of atmospheric conditions. For example, drying can be performed in air at atmospheric pressure. Drying can be performed under high pressure (higher than atmospheric pressure) or under reduced pressure (lower than atmospheric pressure or in a vacuum). Alternatively, drying can be performed in a controlled atmosphere, such as under an inert gas (e.g., nitrogen, helium, or argon) or in the presence of an oxidizing gas (e.g., oxygen or water).
[0090] The performance characteristics of the disclosed AMO nanomaterials are different from those of non-acidified metal oxide nanoparticles. As an example, FIG. 4 shows the difference in the cyclic voltammograms of AMO tin prepared by a single-pot method compared to that of commercially available non-AMO tin when cycled against lithium. For example, the surface-functionalized AMO material shows better reversibility than the non-AMO material. The presence of distinct peaks in the CV of the AMO material may indicate that multiple electron transfer steps are occurring during charge / discharge. For example, the high voltage peaks may indicate direct oxidation / reduction of the AMO material, while the low voltage peaks may be due to changes in the material structure of the AMO material (i.e., alloying).
[0091] As another example, Figure 5 shows that the total reflectance of AMO tin oxide differs from that of commercially available non-AMO tin oxide. The data indicates that AMO has a lower bandgap and therefore more desirable properties as a component of a photovoltaic system in addition to its use as an anode according to the present disclosure.
[0092] AMO materials have the general formula M m O x / G (In the formula, M m O x is a metal oxide, m is 1 or more and 5 or less, and x is 1 or more and 21 or less; G is at least one EWG that is not a hydroxide; ( / simply makes a distinction between metal oxides and EWG, and does not imply a fixed numerical relationship or ratio between the two.) It can be thought of as having the following. G may represent a single type of EWG, or it may represent two or more types of EWG.
[0093] An exemplary AMO is acidified tin oxide (Sn x O y ), acidified titanium dioxide (Ti a O b ), acidified iron oxide (Fe c O d ), and acidified zirconium oxide (Zr e O f Exemplary electron withdrawing groups ("EWG") are Cl, Br, BO 3 , S.O. 4 , P.O. 4 and C.H. 3 According to the present disclosure, regardless of the particular metal or EWG, the AMO material is acidic, but not superacidic, having a pH<7 when suspended at 5 wt % in aqueous solution, and exhibiting H2O at least on its surface. 0 It has a Hammett function of >-12.
[0094] The AMO materials may be crystalline or amorphous in structure (or combinations thereof) and may be utilized alone or in combination with each other as composites, with non-acidified metal oxides, or with other additives, binders, or conductive aids known in the art. In other words, anodes made utilizing the AMOs of the present disclosure may or may not include other materials. In one embodiment, the AMO may be layered onto a conductive material to form the cathode 104. In some embodiments, the AMO material may be added to a conductive aid such as graphite or conductive carbon (or their equivalents) in the range of 10% to 80% by weight and in the range of greater than 90% to 95% by weight. In preferred embodiments, the AMO was added at 10%, 33%, 50%, and 80% by weight.
[0095] To maximize the amount of total available surface area, the AMOs should be in nanoparticulate form (i.e., less than 1 micron in size) and substantially monodisperse. More preferably, the nanoparticulates are less than 100 nm in size, and even more preferably less than 20 nm or less than 10 nm in size.
[0096] In mixed metal AMOs, in addition to the single or binary oxide, another metal or metal oxide is present, and these mixed metal AMOs have been implemented in forming anodes for use in half-cells, cells, and batteries. These mixed metal AMOs have the general formula M m N n O x / G and M m N n R r O x / G (In the formula, M is a metal and m is greater than or equal to 1 and less than or equal to 5; N is a metal, n is greater than zero and is equal to or less than 5; R is a metal and r is greater than zero and less than or equal to 5; O is the total oxygen associated with all metals, and x is greater than or equal to 1, and less than or equal to 21; / simply makes a distinction between metal oxides and electron-withdrawing surface groups, and does not imply a fixed numerical relationship or ratio between the two; G is at least one EWG that is not a hydroxide It can be thought of as having the following. G may represent a single type of EWG, or it may represent two or more types of EWG.
[0097] Some prior art mixed metal oxide systems, of which zeolites are the most prominent examples, exhibit strong acidity, whereas the simple oxides individually do not. Preferred embodiments of the mixed metal AMOs of the present disclosure are those in which the simple M m O xThe mixed metal oxide systems differ from the prior art in that they must contain at least one AMO that is acidic (not super acidic) in the / G form. The preferred mixed metal and metal oxide systems are Sn x Fe c O y+d and Sn x Ti a O y+b where y+d and y+b may be integer or non-integer values.
[0098] In another embodiment, the mixed metal AMO material is prepared by a single-pot method with one modification, i.e., the synthesis starts with salts of two metal precursors in any proportion, instead of one. For example, step 1 of the single-pot method may be modified as follows: first, 3.8 g of tin(II) chloride dihydrate (SnCl 2 2H 2 Dissolve 0.2 g of HO and 0.2 g of lithium chloride (LiCl) in a solution of 20 mL of absolute ethanol and 44 mL of distilled water.
[0099] The salts of the metal precursors shown in Table 1 can be used in any proportion. The salts of the metal precursors can have the same anion group or different anion groups, depending on the product desired. The salts of the metal precursors may be introduced at different times during the synthesis, or may be introduced as solids or in a solvent. In some embodiments, a first metal precursor salt may be used in the primary structure (i.e., a greater proportion) of the resulting AMO, and a second (and optionally a third) metal precursor salt may be added as a dopant or as a minor component of the resulting AMO.
[0100] Experiments with the single-pot method led to seven notable findings. First, in all cases, both surface functionalization and acidity arise endogenously rather than post-synthetically (see FIG. 6). Unlike prior art surface functionalization methods, the single-pot method does not require any additional step or steps for surface functionalization beyond those required to synthesize the metal oxide itself, nor does it utilize hydroxyl-containing organic compounds or hydrogen peroxide.
[0101] Second, the method can be broadly generalized across a wide range of metal oxides and EWGs. Using the disclosed method, iron, tin, antimony, bismuth, titanium, zirconium, manganese, and indium metal oxides were synthesized and simultaneously surface-functionalized with chlorides, sulfates, acetates, nitrates, phosphates, citrates, oxalates, borates, and bromides. Mixed-metal AMOs of tin and iron, tin and manganese, tin and manganese and iron, tin and titanium, indium and tin, antimony and tin, aluminum and tin, lithium and iron, and lithium and tin were also synthesized. In addition, halogens and SO 4 Surface functionalization can be achieved using weaker EWGs that still produce surfaces that are acidic but not super acidic. For example, this method uses acetate (CH 3 COO), oxalate (C 2 O 4 ), and citrate (C 6 H 5 O 7 It was also used to synthesize surface-functionalized AMOs with .Various examples are described below.
[0102] Third, there is a synergistic relationship between EWG and other properties of the nanoparticles, such as size, morphology (e.g., plate-like, spherical, needle-like, or rod-like), oxidation state, and crystallinity (amorphous, crystalline, or a mixture of these). For example, morphology differences can occur between AMO nanoparticles synthesized under identical conditions except for the use of different EWGs for surface functionalization (see FIG. 7). Surface functionalization can act to "freeze" the dimensions of the nanoparticles, halting their growth. This freezing effect may occur in only one dimension of the nanoparticles, or in two or more dimensions, depending on the exact synthesis conditions.
[0103] Fourth, the properties of AMOs are highly sensitive to the synthesis conditions and procedures. For example, differences in the morphology and performance of AMO nanoparticles can occur when synthesized under identical conditions but with two different total reaction times (see Figures 8 and 9). Experimental design approaches can be used to determine the best or optimal synthesis conditions and procedures, which result in a desired property or combination of properties.
[0104] Fifth, both the anions present in the salt of the precursor and the anions present in the acid contribute to the surface functionalization of the AMO. In a preferred embodiment, a tin chloride precursor and hydrochloric acid are used to synthesize the tin AMO. The performance of these particles is different from the embodiment using a tin chloride precursor and sulfuric acid or the embodiment using a tin sulfate precursor and hydrochloric acid. Therefore, in some embodiments, it is preferred to match the anions of the precursor and the acid.
[0105] Sixth, when using precursors with weak EWG and acids with strong EWG, or vice versa, the strongly attractive anions dominate the surface functionalization. This opens up a wider range of synthetic possibilities, using ions that are not readily available in both the precursor salt and the acid. Functionalization can be performed with either strong or weak EWGs. There is also the possibility of mixed functionalization with both strong and weak EWGs. In one example, tin AMOs are synthesized using tin acetate precursors and phosphoric acid. X-ray photoelectron spectroscopy analysis of the surface shows a higher concentration of phosphorus atoms than the bonds associated with the acetate groups (see Figure 10).
[0106] Seventh, and finally, while the disclosed method is a general procedure for the synthesis of AMOs, the synthesis procedure and conditions may be tailored to obtain sizes, morphologies, oxidation states, and crystal states that may be desirable for various applications. As an example, catalytic applications may require AMO materials that are more active in visible light (see FIG. 11A) or more active in ultraviolet light (see FIG. 11B).
[0107] In another example, AMO materials may be used as battery electrodes. A primary (single-use) battery application may require an AMO with properties that provide the highest capacity, while a secondary (rechargeable) battery application may require the same AMO but with properties that provide the best cycling characteristics. Figure 12 compares the cycling characteristics of two different batteries constructed with AMO materials, including a chlorine-containing AMO and a sulfur-containing AMO. AMO materials can improve battery performance without degradation of battery components or gassing (see Figure 13). This is the opposite of what the prior art teaches.
[0108] The cycling characteristics of the battery constructed as an AMO nanomaterial electrode vs. lithium metal half cell are shown in Figure 13, which shows cycling characteristics up to 900 charge / discharge cycles while maintaining useful capacity and exceptional coulombic efficiency. Such long cycling characteristics are particularly remarkable for a lithium metal reference electrode, since lithium metal is known to grow dendrites even at low cycle counts, leading to dendrite expansion and potentially dangerous and catastrophic battery cell failure.
[0109] According to the present disclosure, in a complete cell, an anode 106 comprising the disclosed AMO is coupled to a known electrolyte 108 and lithium cobalt oxide (LiCoO 2 ) and other known materials. Similarly, the materials comprising the separator 110 can be drawn from those currently known in the art.
[0110] In a complete cell, a cathode 104 comprising the disclosed AMO can be utilized with a known electrolyte 108 and an anode 106 comprising known materials, such as carbon on copper foil, that exhibit lower electronegativity than that of the disclosed AMO. Similarly, the materials comprising the separator 110 and electrolyte 108 can be drawn from those currently known in the art, as discussed above.
[0111] Various layering and other strengthening techniques may be deployed to maximize the ability to retain lithium ions to power the cell 100. It should also be understood that batteries based on the AMO cathode 104 according to the present disclosure can be deployed as secondary (e.g., rechargeable) batteries, but can also function as primary batteries. Although the AMO anodes of the present disclosure are suitable for reversible battery chemistries, cells or batteries constructed as described herein may well be deployed as primary cells or batteries.
[0112] In the battery industry, the term "formation" is used to indicate the initial charging or discharging of a battery that occurs at a manufacturing facility before the battery is ready for use. The formation process is generally very slow and may require multiple cycles directed at converting the as-manufactured active materials into a form more accessible to the cell cycle. These transformations The transformation may be a change in the structure, morphology, crystallinity, and / or stoichiometry of the active material.
[0113] Cells and batteries constructed according to the present disclosure, in some embodiments, do not require initial formation and therefore can be used immediately as primary cells or batteries. In other cases, limited formation or rapid formation may be used. Furthermore, by deploying the cells and batteries of the present disclosure as primary batteries that are not intended to be recharged, some of the safety issues that are known in the art to arise more frequently during battery cycling, but that are believed to be inherent to lithium battery chemistry, are mitigated. However, after the initial primary discharge, the cells and batteries disclosed herein are suitable for use as secondary battery systems that may optionally undergo many charge / discharge cycles, such as up to tens, hundreds, or even thousands of cycles.
[0114] In another embodiment according to the present disclosure, the cathode 104 is made of tin oxide (SnO 2 ) nanoparticles, which are not acidified according to the AMO described above. Known electrolytes 108, anodes 106, and separators 110, or as otherwise described in this disclosure, may be utilized in such embodiments.
[0115] It will be understood that other battery configurations are possible using AMO materials. For example, a battery may include a first electrode including an AMO nanomaterial, a second electrode, and an electrolyte disposed between the first and second electrodes. As an example, in a lithium ion battery, the first electrode may operate as a cathode or an anode. For example, in operation as a cathode, the second electrode may correspond to lithium metal, graphite, or another anode material. As another example, in operation as an anode, the second electrode may correspond to LiCoO 2 , LiMn 2 O 4 , LiNiO 2, or another cathode material. Materials useful for the second electrode include, but are not limited to, graphite, lithium metal, sodium metal, lithium cobalt oxide, lithium titanate, lithium manganese oxide, lithium nickel manganese cobalt oxide (NMC), lithium iron phosphate, lithium nickel cobalt aluminum oxide (NCA), or any combination thereof.
[0116] It will be appreciated that the AMO materials disclosed herein may be added as dopants to the anode and / or cathode of a conventional lithium ion cell in amounts between 0.01% and 10% by weight of the AMO material in the electrode, or, for example, in amounts of about 1%, 5% or 10% by weight. The disclosed AMO materials provide a surprising capacity to store lithium atoms, and adding these materials to conventional lithium ion cell electrodes provides these composite capabilities. In one particular example, the electrode may be LiCoO 2 and AMO. In another example, the electrode includes a carbonaceous material, such as graphite, and AMO.
[0117] The AMO materials of the present disclosure may be used with optional acidic components such as binders, acidic electrolytes, or acidic electrolyte additives. The AMO materials of the present disclosure may be in the context of an anode, cathode, half cell, complete cell, integrated battery, or other components. The inventors have surprisingly found that including an acidic component and / or acidic species, such as an organic acid or anhydride, in a battery containing an AMO material increases capacity compared to a battery without the acidic species. Again, the prior art teaches against the use of acidic species, as these species can degrade metal current collectors and housings and cause degradation of other electrode components.
[0118] Comparative data is provided for the cycling performance of AMO-based batteries formed with the same materials and construction, but with standard electrolyte, with basified electrolyte, and with acidified electrolyte, as shown in Figure 14. The batteries included the following constructions: all cathodes contained the same AMO material; all anodes were lithium metal. ;The standard electrolyte is 1M LiPF 6 The electrolyte used was a 1:1:1 mixture of dimethylene carbonate, diethylene carbonate, and ethylene carbonate; the acidified electrolyte was a standard electrolyte containing 3 wt% succinic anhydride; and the basified electrolyte was a standard electrolyte containing 3 wt% dimethylacetamide. All cells were cycled at the same discharge rate. As shown, the cells with the acidified electrolyte system exhibited the best cycling capability and maintained the highest capacity even beyond the maximum number of cycles.
[0119] Figure 15 provides additional comparative cycling performance data for two different batteries with the same battery configuration except that one battery contained an acidified electrolyte and the AMO material in one battery was de-acidified by washing with a solvent. The batteries contained the following configuration: the cathode contained the AMO material; the electrolyte was 1M LiPF 6 The electrolyte was a 1:1:1 mixture of dimethylene carbonate, diethylene carbonate, and ethylene carbonate with 3 wt.% succinic anhydride; the anode was lithium metal. The cells were cycled at the same discharge rate. The cells with the acidified AMO material showed higher capacity retention over cycle number, indicating that the acidified surface of the AMO interacts with the acidified electrolyte, improving performance.
[0120] Several acidic electrolytes have been developed and / or tested and found to work advantageously in the cell chemistries described herein. EXAMPLES
[0121] Example 1 Acetate / chloride functionalized tin oxide AMOs Tin oxide AMO was synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH) 3 COO) 2 ) was dissolved in an ethanol / water solution and acidified by the addition of hydrochloric acid (HCl). The resulting AMO nanomaterial was a soft, gray material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 16 shows a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0122] Example 2 Acetate / sulfate functionalized tin oxide AMOs Tin oxide AMO was synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH) 3 COO) 2 ) in an ethanol / water solution and sulfuric acid (H 2 SO 4 The AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (DPPH). The resulting AMO nanomaterial was a grey, flaky material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 17 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0123] Example 3 Acetate / nitrate functionalized tin oxide AMOs Tin oxide AMO was synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH) 3 COO) 2 ) in an ethanol / water solution to obtain nitric acid (HNO 3The AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (DPPA). The resulting AMO nanomaterial was a grey, flaky material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 18 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0124] Example 4 Acetate / phosphate functionalized tin oxide AMOs Tin oxide AMO was synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH) 3 COO) 2 ) in an ethanol / water solution to obtain phosphoric acid (H 3 PO 4 The AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (DPPA). The resulting AMO nanomaterial was a brown, soft, flaky material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 19 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0125] Example 5 Acetate / citrate functionalized tin oxide AMOs Tin oxide AMO was synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH) 3 COO) 2 ) was dissolved in an ethanol / water solution to obtain citric acid (C 6 H 8 O 7 The AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (DPPA). The resulting AMO nanomaterial was a brown, flaky material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 20 shows a plot of the measured capacity versus cycle number, as well as a plot of the voltage as a function of time during cycling.
[0126] Example 6 Acetate / citrate functionalized tin oxide AMOs Tin oxide AMO was synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH) 3 COO) 2 ) was dissolved in an ethanol / water solution to obtain oxalic acid (C 2 H 2 O 4 The AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (ADH) to the electrolyte. The resulting AMO nanomaterial was a taupe-colored, flaky material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 21 shows a plot of the measured capacity versus cycle number, as well as a plot of the voltage as a function of time during cycling.
[0127] Example 7 Iron oxide doped and acetate / chloride functionalized tin oxide AMOs Doped tin oxide AMOs were synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH) 3 COO) 2 ) was dissolved in an ethanol / water solution containing a small amount of iron acetate. The solution was acidified by the addition of hydrochloric acid (HCl). The resulting AMO nanomaterial was a soft, flaky, creamy grey material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 22 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0128] Example 8 Iron oxide doped and acetate / sulfate functionalized tin oxide AMOs Doped tin oxide AMOs were synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH)3 COO) 2 ) was dissolved in an ethanol / water solution containing a small amount of iron acetate. 2 SO 4 The AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (DPPA). The resulting AMO nanomaterial was a soft, flaky material with a light taupe color that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 23 shows a plot of the measured capacity versus cycle number, as well as a plot of the voltage as a function of time during cycling.
[0129] Example 9 Iron oxide doped and acetate / nitrate functionalized tin oxide AMOs Two doped tin oxide AMO samples were synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH) 3 COO) 2 ) with a small amount of iron acetate (Fe(CH 3 COO) 3 The solution was dissolved in an ethanol / water solution containing nitric acid (HNO 3 The resulting AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (DPPA). The resulting AMO nanomaterial was a soft, white material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 24 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0130] Example 10 Iron oxide doped and acetate / oxalate functionalized tin oxide AMOs Doped tin oxide AMOs were synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH) 3 COO) 2 ) with a small amount of iron acetate (Fe(CH 3 COO) 3) in an ethanol / water solution containing oxalic acid (C 2 H 2 O 4 The resulting AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (DPPA). The resulting AMO nanomaterial was a soft, white material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 25 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0131] Example 11 Iron oxide doped and acetate / phosphate functionalized tin oxide AMOs Doped tin oxide AMOs were synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH) 3 COO) 2 ) with a small amount of iron acetate (Fe(CH 3 COO) 3 ) in an ethanol / water solution. 3 PO 4 The AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (DPPA). The resulting AMO nanomaterial was a white, flaky material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 26 shows a plot of the measured capacity versus cycle number, as well as a plot of the voltage as a function of time during cycling.
[0132] Example 12 Iron oxide doped and acetate / citrate functionalized tin oxide AMOs Doped tin oxide was synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH) 3 COO) 2 ) with a small amount of iron acetate (Fe(CH 3 COO) 3 ) in an ethanol / water solution containing citric acid (C 6 H8 O 7 The AMO nanomaterial was acidified by the addition of 5,000 mol / L of 1,000 mol / L of 1,000 mol / L of 1,000 mol / L. The resulting material did not form particles and was a yellow, glassy, hard material that formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 27 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0133] Example 13 Acetate / bromide functionalized tin oxide AMOs Tin oxide AMO was synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH) 3 COO) 2 ) was dissolved in an ethanol / water solution and acidified by the addition of hydrobromic acid (HBr). The resulting AMO nanomaterial was a grey, soft, powdery material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and charged to zero. The AMO nanomaterial was cycled by discharging to 1.5 V and then charging to 1.5 V. Figure 2628 shows electron microscope images of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of voltage as a function of time during cycling.
[0134] Example 14 Acetate / borate functionalized tin oxide AMOs Tin oxide AMO was synthesized using a single-pot hydrothermal synthesis method. In summary, tin acetate (Sn(CH) 3 COO) 2 ) in an ethanol / water solution to obtain boric acid (H 3 BO 3The AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (DPPA). The resulting AMO nanomaterial was a grey, flaky material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 29 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0135] Example 15 Manganese oxide doped and sulfate / chloride functionalized tin oxide AMOs Doped tin oxide AMO was synthesized using a single-pot hydrothermal synthesis method. 4 ) with a small amount of manganese chloride (MnCl 2 ) in an ethanol / water solution. 2 SO 4 The AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (DPPA). The resulting AMO nanomaterial was a very soft tan material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 30 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of voltage as a function of time during cycling.
[0136] Example 16 Manganese oxide doped and chloride functionalized tin oxide AMOs Doped tin oxide AMOs were synthesized using a single-pot hydrothermal synthesis method. 2 ) with a small amount of manganese chloride (MnCl 2) into an ethanol / water solution containing 1,2-dichloro-1,3-tetrahydrofuran (AMO) and 1,2-dichloro-1,3-tetrahydrofuran (1,3-tetrahydrofuran). This solution was acidified by the addition of hydrochloric acid (HCl). The resulting AMO nanomaterial was a soft grey-brown material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 31 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0137] Example 17 AMOs of tin oxide doped with iron oxide and aluminum oxide and functionalized with chloride Two doped tin oxide AMO samples were synthesized using a single-pot hydrothermal synthesis method. In summary, tin chloride (SnCl 2 ) with a small amount of iron chloride (FeCl 3 ) and aluminum chloride (AlCl 3 ) in an ethanol / water solution containing both ZnO and ZnO. The solution was acidified by the addition of hydrochloric acid (HCl). The resulting first sample of AMO nanomaterial was a light tan flaky material and formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts and then charging to 1.5 volts. Figure 32 shows a plot of the measured capacity versus cycle number, and a plot of voltage as a function of time during cycling. The resulting second sample of AMO nanomaterial was a light gray flaky material.
[0138] Example 18 Iron oxide AMOs doped with tin oxide and functionalized with chloride Doped iron oxide AMOs were synthesized using a single-pot hydrothermal synthesis method. 3 ) with a small amount of tin chloride (SnCl 2) in an ethanol / water solution containing 1,2-dichloro-1,3,4-tetramethylphenylacetone (AMO) and 1,2-dichloro-1,3,4-tetramethylphenylacetone (TAP). The iron to tin ratio was 95:5. The solution was acidified by the addition of hydrochloric acid (HCl). The resulting AMO nanomaterial was a soft red material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 33 shows a plot of the measured capacity versus cycle number and a plot of the voltage as a function of time during cycling.
[0139] Example 19 Iron oxide AMOs doped with tin oxide and functionalized with chloride Doped iron oxide AMOs were synthesized using a single-pot hydrothermal synthesis method. 3 ) with a small amount of tin chloride (SnCl 2 ) in an ethanol / water solution containing 100% iron and 100% tin. The iron to tin ratio was 95:5. The solution was acidified by the addition of hydrochloric acid (HCl). The resulting AMO nanomaterial was a black glassy material and was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 34 shows a plot of the measured capacity versus cycle number and a plot of the voltage as a function of time during cycling.
[0140] Example 20 Nitrate-functionalized iron oxide AMOs Iron oxide AMO was synthesized using a single-pot hydrothermal synthesis method. In summary, iron nitrate Fe(NO 3 ) 3 was dissolved in an ethanol / water solution to obtain nitric acid (HNO 3 The AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (ADHES). The resulting AMO nanomaterial was a black glassy material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 35 shows a plot of the measured capacity versus cycle number, as well as a plot of the voltage as a function of time during cycling.
[0141] Example 21 Chloride-functionalized bismuth oxide AMOs Bismuth oxide AMO was synthesized using a single-pot hydrothermal synthesis method. 3 ) was dissolved in an ethanol / water solution and acidified by the addition of hydrochloric acid (HCl). The resulting AMO nanomaterial was a soft white material and formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 36 shows a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0142] Example 22 AMOs of sulfate-functionalized zirconium oxide. Zirconium oxide AMO was synthesized using a single-pot hydrothermal synthesis method. In summary, zirconium sulfate (Zr(SO) 4 ) 2 ) in an ethanol / water solution and sulfuric acid (H 2 SO 4 The AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (DPPA). The resulting AMO nanomaterial was a flaky, white material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 37 shows a plot of the measured capacity versus cycle number, as well as a plot of the voltage as a function of time during cycling.
[0143] Example 23 Sulfate-functionalized titanium dioxide AMO Titanium oxide AMO was synthesized using a single-pot hydrothermal synthesis method. 4 ) in an ethanol / water solution and sulfuric acid (H 2 SO 4The resulting AMO nanomaterial was a white, flaky material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 38 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of voltage as a function of time during cycling.
[0144] Example 24 Sulfate-functionalized antimony oxide AMOs Antimony oxide AMO was synthesized using a single-pot hydrothermal synthesis method. 2 (SO 4 ) 3 ) in an ethanol / water solution and sulfuric acid (H 2 SO 4 The AMO nanomaterial was acidified by the addition of 1,2-dichlorophenyl ether (DPPA). The resulting AMO nanomaterial was a very soft white material that was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 39 shows a plot of the measured capacity versus cycle number, as well as a plot of the voltage as a function of time during cycling.
[0145] Example 25 Chloride-functionalized indium oxide AMOs Indium oxide AMO was synthesized using a single-pot hydrothermal synthesis method. 3 ) was dissolved in an ethanol / water solution and acidified by the addition of hydrochloric acid (HCl). The resulting AMO nanomaterial was a white material and formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 40 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0146] Example 26 Sulfate-functionalized indium oxide AMOs Indium oxide AMO was synthesized using a single-pot hydrothermal synthesis method. 2 (SO 4 ) 3 ) in an ethanol / water solution and sulfuric acid (H 2 SO 4 The resulting AMO nanomaterial was acidified by the addition of 5,000 mol / L of 1,000 mol / L of 1,000 mol / L of 1,000 mol / L. The resulting AMO nanomaterial was a white material and was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 41 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0147] Example 27 Bromide-functionalized indium oxide AMOs Indium oxide AMO was synthesized using a single-pot hydrothermal synthesis method. 3 ) was dissolved in an ethanol / water solution and acidified by the addition of hydrobromic acid (HBr). The resulting AMO nanomaterial was a blue-white material and formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 42 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0148] Example 28 Chloride-functionalized indium oxide AMOs Indium oxide AMO was synthesized using a single-pot hydrothermal synthesis method. 3) was dissolved in an ethanol / water solution and acidified by the addition of hydrochloric acid (HCl). The resulting AMO nanomaterial was gray with a yellow ring and formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 43 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0149] Example 29 Mixed lithium and iron oxide AMOs doped with tin oxide and functionalized with chloride / acetate Doped mixed lithium oxide and iron oxide AMOs were synthesized using a single-pot hydrothermal synthesis method. In summary, lithium acetate (Li(CH) 3 COO) and ferric chloride (FeCl 3 ) and a small amount of tin chloride (SnCl 2 The AMO nanomaterial was dissolved in an ethanol / water solution containing 1,2-dichlorophenyl ether (DPPA). The solution was acidified by the addition of hydrochloric acid (HCl). During the synthesis, a tan-pinkish color with a green ring developed in the flask. However, the final AMO nanomaterial was gray in color and formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 44 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0150] Example 30 Mixed lithium and iron oxide AMOs doped with tin oxide and functionalized with chloride / acetate Doped mixed lithium oxide and iron oxide AMOs were synthesized using a single-pot hydrothermal synthesis method. In summary, lithium acetate (Li(CH) 3 COO) and ferric chloride (FeCl 3 ) and a small amount of tin chloride (SnCl 2The AMO nanomaterial was dissolved in an ethanol / water solution containing 1,2-dichlorophenyl ether (DPPA). This solution was acidified by the addition of hydrochloric acid (HCl). The resulting AMO nanomaterial was a pale gold colored material and was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 45 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0151] Example 31 Mixed lithium and iron oxide AMOs doped with tin oxide and functionalized with chloride / acetate Doped mixed lithium oxide and iron oxide AMOs were synthesized using a single-pot hydrothermal synthesis method. In summary, lithium acetate (Li(CH) 3 COO) and ferric chloride (FeCl 3 ) and a small amount of tin chloride (SnCl 2 The AMO nanomaterial was dissolved in an ethanol / water solution containing 1,2-dichlorophenyl ether (DPPA). This solution was acidified by the addition of hydrochloric acid (HCl). The resulting AMO nanomaterial was a thin milky white material and was formed into an electrode. The electrode was incorporated into a battery cell against lithium metal and cycled by discharging to zero volts followed by charging to 1.5 volts. Figure 46 shows an electron microscope image of the AMO nanomaterial, a plot of the measured capacity versus cycle number, and a plot of the voltage as a function of time during cycling.
[0152] At present, lithium batteries are recognized as a safety risk in certain circumstances. For example, airline regulations now require partial discharge of lithium batteries carried in cargo holds. There have been reports of fires resulting from runaway exothermic reactions in devices using lithium batteries. Additionally, commonly deployed fire suppression systems and equipment: Lithium fires can be difficult to extinguish, and for this reason lithium-containing compounds are used in many commercial battery cells rather than metallic lithium.
[0153] However, using lithium-containing compounds in the anode rather than lithium metal may limit the amount of lithium available to react and absorb into the cathode during discharge, and therefore may limit the capacity of such cells. However, the AMO materials disclosed herein not only absorb more lithium during discharge, but also show improved safety characteristics. For example, when battery cells containing AMO materials in the cathode and lithium metal electrodes are subjected to safety tests such as nail penetration tests, short circuit tests, and overvoltage tests, the batteries perform well and do not appear to pose an unacceptable risk of fire or explosion. This may be because the AMO passivates the lithium metal in the cell or battery. Even with the use of solid or pure lithium as the anode, devices using the AMO of the present disclosure as the cathode do not appear to pose an unacceptable risk of fire or explosion. The novel safety results may also be due to the lower operating voltage of cells constructed according to the present disclosure, which in some embodiments is <1.5V compared to conventional lithium-ion operating voltages >3.0V.
[0154] The AMO (SnO 2 Several cells were constructed with a cathode containing AMO (SnO 2 The composition was prepared from a mixture of polyvinylidene fluoride (PVDF), Ketjen Black (KB), polyvinylidene fluoride (PVDF), and polyarylamide (PAA) in a volume ratio of 63 / 10 / 26.1 / 0.9. The double-sided layer of this composition was 4 mg / cm per side. 2 Six of these layers constituted the cathode. The area of the prepared cathode was 9 × 4 cm 2 The separator was obtained from Targray Technology International, Inc. and contained a 25 μm thick layer of polypropylene. The separator area was 9.4 × 4.4 cm 2 The electrolyte was 1M LiPF in a solvent of ethylene carbonate, diethyl carbonate, and dimethyl carbonate in a 1 / 1 / 1 volume ratio. 6 The anode was prepared from a 9.2 × 4.2 cm 2, a 50 μm thick layer of lithium metal.
[0155] Two of the constructed cells were discharged prior to safety testing, and the actual capacity of these cells was 1.7 Ah and the specific capacity was 1575 mAh / g SnO 2 It was found that:
[0156] Figure 47 is a plot of temperature and voltage for a cell constructed as above and subjected to a nail penetration test. The test was performed at room temperature and no events (such as fire) were observed. It can also be seen that the temperature and voltage remain stable.
[0157] FIG. 48A is a plot of temperature and voltage of a cell constructed as described above and subjected to an overcharge test. A current of 1 A was applied. No adverse events were observed over the test period, except for gas evolution from the cell. FIG. 48B is a plot of the overcharge test of FIG. 48A focusing on the start of the test.
[0158] It should be understood that the examples constructed for penetration testing purposes are not intended to be limiting with respect to the entire disclosure herein. Cells and batteries of various sizes, capacities, and materials may be constructed in accordance with the present disclosure. Utilizing the AMOs of the present disclosure, such batteries will benefit from the improved safety demonstrated herein, whether such safety is ultimately due to lithium passivation, low voltage, or other factors.
[0159] Embodiments of electrochemical cells constructed incorporating AMO materials as the cathode and lithium as the electrode have been tested to successfully undergo up to 900 or more charge-discharge cycles without catastrophic, destructive failure. Embodiments of electrochemical cells constructed incorporating lithium as the electrode have been tested to successfully undergo up to 900 or more charge / discharge cycles and still retain a charge and maintain useful capacity.
[0160] Without wishing to be bound by any theory, the improved safety provided by the use of AMO-based cathode materials in lithium batteries may result from the ability of the AMO materials to passivate metallic lithium and prevent the formation of dendrites. The inventors observed that upon cycling, metallic lithium anodes did not appear to grow or form dendrites, but rather the lithium anodes exhibited a softer, less crystalline structure. In some embodiments, the lithium anode may be passivated, such as by cycling, as a component of an electrochemical cell described herein, and then removed from the electrochemical cell and used as an electrode in a new electrochemical cell with a different cathode. In addition, cells constructed according to the present disclosure utilize low operating voltages, such as between 1-2 volts, which contrasts with the typical voltages of lithium or lithium-ion battery cells, which typically operate at about 3-4.2 volts. Such differences in operating voltages may partially explain the safety of the disclosed cells.
[0161] With respect to cell or battery constructions using lithium as the anode according to the present disclosure, in some embodiments, the entire anode (100%) is metallic lithium. The metallic lithium need only be substantially pure in that a small percentage of the anode may contain trace elements and impurities that do not measurably affect the performance of the cell or battery. In various embodiments, the anode comprises at least 50%, 55%, 60%, 65%, 75%, 80%, 85%, 90%, or 95% metallic lithium.
[0162] For purposes of this disclosure, the term "metallic lithium" refers to lithium in its neutral atomic state (i.e., non-ionic state). The term metallic lithium is intended to distinguish it from other forms of lithium, including lithium ions and lithium compounds. The term metallic lithium may refer to neutral atomic lithium present in a mixture that includes lithium atoms, such as a mixture of lithium and other elements, compounds, or substances. The term metallic lithium may refer to neutral atomic lithium present in a lithium alloy, such as a metal mixture that includes lithium and one or more other metals. The term metallic lithium may refer to neutral atomic lithium present in a composite structure that includes lithium and one or more other materials. It will be understood that an electrode comprising or including metallic lithium may include other materials in addition to lithium, although metallic lithium may correspond to the active material of such an electrode. In some cases, the anode of an electrochemical cell includes metallic lithium.
[0163] For purposes of this disclosure, metallic lithium may be taken to mean lithium that has not reacted with other elements to form compounds (at least during construction of the battery or cell). In some embodiments, a portion of the anode may be metallic lithium and a portion of the anode may be a lithium compound containing various percentages of lithium that has reacted with other elements to form lithium compounds. The metallic lithium may be disposed on or within the anode such that it is geometrically separated relative to the lithium compound portion of the anode.
[0164] All references throughout this application, such as patent documents, including issued or granted patents or equivalents, patent application publications, and non-patent literature documents, or other materials, are incorporated by reference in their entirety herein, as if each was individually incorporated by reference.
[0165] All patents and publications mentioned in this specification are indicative of the level of skill of those skilled in the art to which this invention pertains. No. 6,393,311, filed on Dec. 13, 2003, and which is hereby incorporated by reference in its entirety to demonstrate the state of the art in this application, and it is intended that this information may be used herein, if necessary, to exclude (e.g., disclaim) certain embodiments that are in the prior art. For example, if a compound is claimed, it should be understood that compounds known in the prior art, including specific compounds disclosed in the references disclosed herein (particularly referenced patent documents), are not intended to be included in the claim.
[0166] When a group of substituents is disclosed herein, it is understood that all individual members of the group, and all subgroups and classes that can be formed using the substituents are disclosed separately.When a Markush group or other grouping is used herein, all individual members of the group, and all possible combinations and subcombinations of the group are individually included in the disclosure.As used herein, "and / or" means that one, all, or any combination of the items in the list separated by "and / or" is included in the list; for example, "1, 2, and / or 3" is equivalent to "1" or "2" or "3", or "1 and 2" or "1 and 3" or "2 and 3", or "1, 2, and 3".
[0167] Unless otherwise stated, the present invention can be practiced using any combination or formulation of components described or exemplified. The specific names of materials are intended to be exemplary, and it is recognized that one skilled in the art can give different names to the same materials. One skilled in the art will understand that methods, device elements, starting materials, and synthetic methods other than those specifically exemplified can be used in the practice of the present invention without resorting to undue experimentation. All art-known functional equivalents of such methods, device elements, starting materials, and synthetic methods are intended to be included in the present invention. When ranges are given herein, for example, temperature ranges, time ranges, or composition ranges, all intermediate ranges and subranges, and all individual values included in the given ranges are intended to be included in the present disclosure.
[0168] As used herein, "comprising" is synonymous with "including," "containing," or "characterized by," is inclusive or open-ended, and does not exclude additional, unrecited elements or method steps. As used herein, "consisting of" excludes any element, step, or ingredient not specified in the claim element. As used herein, "consisting essentially of" does not exclude materials or steps that do not materially affect the basic and novel characteristics of the claim. Recitations herein of the term "comprising," particularly in describing components of a composition or in describing elements of a device, are understood to encompass compositions and methods that consist essentially of and consist of the recited components or elements. The invention illustratively described herein can be suitably practiced in the absence of any element or limitation not specifically disclosed herein.
[0169] The terms and expressions used are used as terms of description and not of limitation, and there is no intention in the use of such terms and expressions to exclude the features shown and described or equivalents of portions thereof, recognizing that various modifications are possible within the scope of the invention as described in the claims. Thus, although the present invention has been specifically disclosed by preferred embodiments and optional features, it should be understood that modifications and variations of the concepts disclosed herein may be possible by those skilled in the art, and such modifications and variations are considered to be within the scope of the invention as defined by the claims. [Mode of the invention] [1] A battery cell comprising an anode, an electrolyte, and a cathode, wherein one of the anode or the cathode comprises at least one solid metal oxide nanomaterial comprising an acidic, but not super-acidic, surface, the surface having a pH of less than 5 when resuspended at 5% by weight in water after drying, and a Hammett function H of greater than -12. 0 wherein at least a portion of the anode is made of metallic lithium. [2] 2. The battery cell of claim 1, wherein the solid metal oxide nanomaterial has at least one particle dimension less than 100 nm in size. [3] 2. The battery cell of claim 1, wherein the solid metal oxide nanomaterial has at least one particle dimension less than 20 nm in size. [4] 2. The battery cell of claim 1, wherein the solid metal oxide nanomaterial has at least one particle dimension less than 10 nm in size. [5] 2. The battery cell of claim 1, wherein the solid metal oxide nanomaterial comprises a substantially monodisperse nanoparticle morphology. [6] The surface has a pH of less than 4 when dried and resuspended at 5% by weight in water, and a Hammett function H of greater than -12. 0 2. The battery cell according to claim 1, [7] The surface has a pH of less than 3 when dried and resuspended at 5% by weight in water, and a Hammett function H of greater than -12. 0 2. The battery cell according to claim 1, [8] 1. A battery cell having an electrode comprising at least one solid metal oxide material, said metal oxide being substantially monodisperse and surface functionalized with a material providing acidic electron-withdrawing groups having a molecular weight of less than 200, and a counter electrode comprising at least 50% metallic lithium when said battery cell is constructed. [9] The material that surface functionalizes the surface of the metal oxide is acidic but not superacidic, having a pH of less than 7 when suspended at 5 wt % in an aqueous solution, and a Hammett function H of greater than -12. 0 9. The battery cell according to claim 8,
[10] The material that surface functionalizes the surface of the metal oxide is acidic but not superacidic, having a pH of less than 5 when suspended at 5 wt % in an aqueous solution, and a Hammett function H of greater than -12. 0 10. The battery cell according to claim 9,
[11] 10. The battery cell of claim 9, wherein when the battery cell is constructed, the counter electrode is 95% or more metallic lithium.
[12] 10. The battery cell of claim 9, wherein when the battery cell is constructed, a surface of the counter electrode comprises pure metal.
[13] 10. The battery cell of claim 9, wherein when the battery cell is constructed, at least a geometric portion of the counter electrode comprises metallic lithium.
[14] M m O x A battery cell having a cathode comprising a solid metal oxide nanomaterial of M morphology, m is a metal, and O x is the total oxygen, and M m O xis a metal oxide, G is at least one electron-withdrawing surface group, and " / " distinguishes between the metal oxide and the electron-withdrawing surface group, and the battery electrode solid metal oxide nanomaterial has, at least on its surface, a pH of less than 5 when dried and resuspended at 5 wt % in water, and a Hammett function H of greater than -12. 0 wherein the anode of the battery comprises at least 50% metallic lithium that does not react with other elements during construction of the battery cell.
[15] The solid metal oxide nanomaterial constituting the cathode is a second, different metal, "N n 15. The battery cell according to claim 14,
[16] The solid metal oxide nanomaterial constituting the cathode is a third different metal "R r 16. The battery cell according to claim 15, further comprising:
[17] 15. The battery cell of claim 14, further comprising an anode of a non-acidic material.
[18] 15. The battery cell of claim 14, wherein the anode comprises at least 95% metallic lithium.
[19] providing a metallic lithium anode in the battery cell; Providing in the battery cell a cathode comprising at least one solid metal oxide nanomaterial comprising a surface that is acidic but not very acidic, the surface having a pH of less than 5 when resuspended at 5% by weight in water after drying, and a Hammett function H of greater than -12. 0 and The method includes:
[20] A method of passivating a metallic lithium anode in a battery cell comprising providing in the battery cell a cathode comprising at least one solid metal oxide nanomaterial comprising an acidic, but not very acidic, surface, the surface having a pH of less than 5 when resuspended at 5% by weight in water after drying, and a Hammett function H of greater than -12. 0 The method comprises the steps of: [twenty one] A battery cell comprising an anode, an electrolyte, and a cathode, one of the cathodes comprising at least one solid metal oxide nanomaterial comprising an acidic, but not super-acidic, surface, the surface having a pH of less than 5 when resuspended at 5% by weight in water after drying, and a Hammett function H of greater than -12. 0 wherein at least a portion of the anode consists essentially of metallic lithium.
Claims
1. an anode comprising metallic lithium; and A cathode comprising a tin oxide nanomaterial in an amount of 15% or less by weight of the active material of the cathode, said tin oxide nanomaterial having a particle size of less than 100 nm, and said tin oxide nanomaterial being surface functionalized with at least one electron-withdrawing group selected from the group consisting of Cl, Br, BO3, SO4, PO4, NO3, CH3COO, C2O4, C2H2O4, C6H8O7, and C6H5O7; A battery cell including:
2. 10. The battery cell of claim 1, further comprising the tin oxide nanomaterial having a particle size of less than 100 nm in solid form doped with at least one of iron oxide, manganese oxide, or titanium oxide.
3. 3. The battery cell of claim 2, wherein the iron oxide, manganese oxide or titanium oxide is an acidified form of the iron oxide, manganese oxide or titanium oxide, respectively.
4. 4. The battery cell of claim 3, wherein the acidified form has a pH of less than 5 measured when the acidified form is dried and suspended in water at 5% by weight.
5. The iron oxide, manganese oxide or titanium oxide is not particularly limited. 3 , S.O. 4 , P.O. 4 , NO 3 , C.H. 3 COO, C 2 O 4 , C 2 H 2 O 4 , C 6 H 8 O 7 , and C 6 H 5 O 7 4. The battery cell of claim 3, wherein the battery cell is surface-functionalized with at least one electron-withdrawing group selected from the group consisting of:
6. 2. The battery cell of claim 1, wherein the tin oxide nanomaterial is 10% or less by weight of the cathode active material.
7. 10. The battery cell of claim 1, wherein the tin oxide nanomaterial is an acidified form of tin oxide.
8. 8. The battery cell of claim 7, wherein the acidified form has a pH of less than 5 measured when dried and suspended in water at 5% by weight.
Citation Information
Patent Citations
Low Dissolution Rate Coated Metal Oxide Particles, Methods of Making and Using Them in Electrochemical Systems
JP2009524568A